Processintern metananrikning - Hävermark, Ulf (2016)
Small scale biogas plants (max digester volume 1000 m3) in Sweden produced in average 1.26 GWh per plant in 2014. Most of the biogas was used for combined heat and power production. The relatively cheap electricity in Sweden makes this a low profit business. If the biogas is upgraded to vehicle fuel its value will increase. However, upgrading biogas with conventional methods is costly, and for small scale biogas plants this cost cannot be justified. Development of alternative upgrading methods is an option to decrease the cost of upgrading and making small scale vehicle fuel production a reality. In this master thesis the upgrading method known as in-situ methane enrichment was investigated. This method involves desorption of carbon dioxide in the sludge using a desorption chamber separated from the digester. Air is blown through the sludge for desorption of carbon dioxide. Subsequently, the sludge is pumped back to the digester. The aim was to perform an energy mapping on the enrichment facility installed at the biogas plant (260 m3) at Sötåsens naturbruksgymnasium. In addition, the possibility to absorb ammonium-nitrogen in the off-gas from the process using a scrubber was also investigated in laboratory-scale. The results showed that the upgrading facility lost large quantities of heat during operation. During the coldest circumstances using an air flow of 260 m3/h through the sludge, the heat loss was 495 kWh/day. The corresponding efficiency of carbon dioxide removal was 7.6 kWh/m3 removed carbon dioxide. With proper insulation and heat recovery, the facility has the potential to decrease the heat demand to ca 139 kWh/day, giving an efficiency of 2.3 kWh/m3 removed carbon dioxide. The electric efficiency was 1 kWh/m3 removed carbon dioxide. The laboratory test of ammonium-nitrogen absorption indicated that the plant has a potential to absorb 59 – 275 kg nitrogen/year by installing a scrubber with a volume of 122 l. The economic benefits are small, but other values such as reduced ammonia pollution or heat recovery solutions using a scrubber should be considered.